Disiplin dalam Pendidikan: Perspektif Alkitab Amsal 13:24 dan Praktik Kontemporer Pada Satuan Pendidikan Kristen Anak Usia Dini - Paembonan, Yanni (PEADA': Jurnal Pendidikan Kristen, 2024)
The aim of this research is to explore the biblical perspective on physical violence in child education and to analyze the relevance of discipline implementation according to Proverbs 13:24 within the context of early childhood Christian education. The methodology employed is a qualitative approach focusing on literature review, including hermeneutic analysis of biblical texts and descriptive methods to explain the early childhood education system in Indonesia. The underlying theory emphasizes the integration of Christian values in education and the importance of educating children without violence. The findings indicate that although physical punishment is still practiced in Christian education, there is an urgent need to develop a more humane disciplinary approach that aligns with the principles of love and understanding found in the Bible, in order to support the holistic growth and development of children.